Caracterización morfológica de 92 accesiones del cultivo de achiote (Bixa orellana) del banco de germoplasma del INIAP (EETP) - Quishpe Franco, Melissa Mishell (2022)
The present investigation was carried out at the INIAP Pichilingue Tropical Experimental Station located in the Mocache canton km 5.5 of the Vía Quevedo-El Empalme. The objective of this research was to morphologically characterize 92 accessions of achiote (Bixa orellana) established in the germplasm bank of the Station, the accessions were collected in